Determinants and Prediction Equations of Six-Minute Walk Test Distance Immediately After Cardiac Surgery - Radi, Basuni; Ambari, Ade Meidian; Dwiputra, Bambang; Intan, Ryan Enast; Triangto, Kevin; Santoso, Anwar; Setianto, Budhi (Frontiers in Cardiovascular Medicine, 2021)
Background: To date, there is no reference for a 6-min walk test distance (6-MWD) immediately after cardiac surgery. Therefore, this study aimed to identify the determinants and to generate equations for prediction reference for 6-MWD in patients immediately after cardiac surgery. Methods: This is a cross-sectional study of the 6-min walk test (6-MWT) prior to participation in the cardiac rehabilitation (CR) program of patients after coronary artery bypass surgery (CABG) or valve surgery. The 6-MWT were carried out in a gymnasium prior to the CR program immediately after the cardiac surgery. Available demographic and clinical data of patients were analyzed to identify the clinical determinants of 6-MWD. Results: This study obtained and analyzed the data of 1,509 patients after CABG and 632 patients after valve surgery. The 6-MWD of all patients was 321.5 ± 73.2 m (60–577). The distance was longer in the valve surgery group than that of patients in the CABG group (327.75 ± 70.5 vs. 313.59 ± 75.8 m, p < 0.001). The determinants which significantly influence the 6-MWD in the CABG group were age, gender, diabetes, atrial fibrillation, and body height, whereas in the valve surgery group these were age, gender, and atrial fibrillation. The multivariable regression models generated two formulas using the identified clinical determinants for patients after CABG: 6-MWD (meter) = 212.57 + 30.47 (if male gender) − 1.62 (age in year) + 1.09 (body height in cm) − 12.68 (if with diabetes) − 28.36 (if with atrial fibrillation), and for patients after valve surgery with the formula: 6-MWD (meter) = 371.05 + 37.98 (if male gender) − 1.36 (age in years) − 10.61 (if atrial with fibrillation). Conclusion: This study identified several determinants for the 6-MWD and successively generated two reference equations for predicting 6-MWD in patients after CABG and valve surgery.